Antipseudomonal β-Lactams Resistance in Iran - Rabiei, Mohammad Mahdi (Int J Microbiol, 2020)
Over the last years, the mortality rate of Pseudomonas aeruginosa, which is one of the major reasons for severe infections, has been significantly increasing. This bacterium is highly resistant to many antibiotics, especially carbapenems, thanks to its complicated mechanism by which it can acquire exogenous genes. The purpose of this research is to have a review of empirical studies surveying the P. aeruginosa resistance to beta-lactams in Iran in order to investigate the most reliable methods by which the incidence of P. aeruginosa infections can be decreased and controlled. We performed a systematic review of all articles published from 2008 until 2018. Studies which did not address P. aeruginosa resistance to beta-lactams were excluded from the analysis. Studies with less than 10 cases were also excluded. Studies with more than ten cases, which did not have repetitive information, were taken into account for the final selection; 133 out of 893 articles were chosen. The resistance rate of P. aeruginosa among the articles was as follows: more than 72% of studies revealed >50% level of resistance to cefepime, followed by aztreonam (53.2%), ceftazidime (61%), piperacillin/tazobactam (54.5%), meropenem (48.3%), and imipenem (42.4%). The selection of empiric antipseudomonal antibiotics is absolutely uncertain and hazardous, and the risk of clinical failure may be more among cephalosporins and piperacillin-tazobactam as well as aztreonam. The results of this study illustrate that the methods enabling clinics to identify the bacterium resistance pattern and its genetic basis and to have the opportunity of empiric therapies through access to updated local data of antimicrobial susceptibility pattern are the most effective methods. However, the widespread usage of these approaches undoubtedly needs reliable molecular and nucleic acid-based devices, which are both affordable and available.